Особливості хронотопу у збірці Володимира Затуливітра «Зоряна речовина» - Мендель, Ю. (Літературознавчі обрії. Праці молодих учених, 2010)
The chronotop of Volodymyr Zatulyviter’s poetry collection «Zoryana rechovyna» («Star substance») has two levels: conceptual and perceptional. It is also divided into strata: astronomic, mythological, historical, philosophic. There are two special strata: cinematographic and dream. They influence the unique and rich metalogy of the poetry, the plot and structure of the texts. The chronotop subordinates all other nature philosophic categories. These are Form, Substance, Motion and dialectical categories.